The trigger - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Bantam Books, 2000)
A scientist discovers a device that detonates explosives, in bullets and bombs. The device, Trigger, is thus able to do away with gunpowder-based weapons, but can it be allowed? The gun lobby and the army want it banned and a pro-Trigger senator is assassinated.